2022
DOI: 10.3389/fpls.2022.1014282
|View full text |Cite
|
Sign up to set email alerts
|

Novel candidate loci for morpho-agronomic and seed quality traits detected by targeted genotyping-by-sequencing in common bean

Abstract: Phaseolus vulgaris L., known as common bean, is one of the most important grain legumes cultivated around the world for its immature pods and dry seeds, which are rich in protein and micronutrients. Common bean offers a cheap food and protein sources to ameliorate food shortage and malnutrition around the world. However, the genetic basis of most important traits in common bean remains unknown. This study aimed at identifying QTL and candidate gene models underlying twenty-six agronomically important traits in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“… *(1) González et al ( 2016 ), (2) Berry et al ( 2020 ), (3) Murube et al ( 2020 ), (4) Bassett et al ( 2021 ), (5) Arriagada et al ( 2022 ), (6) Giordani et al ( 2022 ), (7) Ugwuanyi et al ( 2022 ) …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… *(1) González et al ( 2016 ), (2) Berry et al ( 2020 ), (3) Murube et al ( 2020 ), (4) Bassett et al ( 2021 ), (5) Arriagada et al ( 2022 ), (6) Giordani et al ( 2022 ), (7) Ugwuanyi et al ( 2022 ) …”
Section: Resultsmentioning
confidence: 99%
“…Well-characterized QTL, consistent among backgrounds, well delimited and tagged, and with a significant contribution to the expression of the trait are desirable for use in breeding. A few studies have reported QTL for seed size and shape (González et al 2016 ; Murube et al 2020 ; Bassett et al 2021 ; Giordani et al 2022 ; Ugwuanyi et al 2022 ; Arriagada et al 2022 ) and seed quality traits (Berry et al 2020 ; Bassett et al 2021 ). The results allowed the identification of 13 consistent genomic regions associated with QTL that were previously reported in different genetic backgrounds and environments, indicating the relevance of such regions in the control of seed characters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations